Pharmaceutical equivalence of gabapentin tablets with various extragranular binders - Swati Jagdale; Bhanudas Kuchekar; Jibanananda Satapathy; Aniruddha Chabukswar (São Paulo State University (UNESP), 2010)
Gabapentin is widely used as an oral anti-epileptic agent. However, owing to its high crystallinity and poor compaction properties, it is difficult to form tablets of this drug by direct compression. The aim of this study was to develop gabapentin tablets, pharmaceutically equivalent to the brand-name pioneer product Neurontin®(marketed in USA). Gabapentin 800mg tablets were produced by wet granulation with a constant concentration of intragranular binder and a varying concentration of extragranular binders (A = polyvinylpyrrolidone K30, B = hydroxypropylmethylcellulose 15 cps, C = Kollidon VA64, D =Klucel EXF). The tablets that did not vary in weight, thickness or hardness and had appropriate friability and disintegration profiles were coated with a 3% film-coating solution. Seven formulations F1 (A 3%), F2 (A 6%), F3 (B 3%), F4 (B 6%), F5 (C 3%), F6 (C 3%) and F7 (D 3%) were prepared. Among these, F6 exhibited adequate hardness, friability, disintegration, uniformity of content and total drug dissolution after 45minutes. Comparing the F6 dissolution profile with that of the brand-name tablets, the difference factor (f1) was 5.93 and the similarity factor (f2) 67.85. Hence, formulation F6 was found to be equivalent to Neurontin®.